Pines and other conifers in Thailand: a Quaternary relic? - Werner, Wolfgang L. (Journal of quaternary science, 1997)
In the forests of Thailand there are a number of conifer species from various families. Those growing in mountains have disjunct areas which cannot explain their present occurrence. Fossil evidence is scarce but indicates that in Quaternary the areas were larger.
First published: 04 December 1998
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 29.06.2021